Cytochrome b reducible by succinate in an isolated succinate dehydrogenase-cytochrome b complex from Bacillus subtilis membranes. - Hederstedt, L (1980)
In previous work with membranes of Bacillus subtilis, the succinate dehydrogenase complex was isolated by immunoprecipitation of Triton X-100-solubilized membranes. The complex included a polypeptide with an apparent molecular weight of 19,000, probably attributable to apocytochrome. This paper reports the further characterization of this cytochrome and its relation to the respiratory chain of B. subtilis. The cytochrome was identified as cytochrome b, and its difference absorption spectra showed maxima at 426, 529, and 558 nm at room temperature. The oxidized cytochrome had an absorption maximum at 413 nm. The cytochrome was reduced by succinate in the isolated succinate dehydrogenase complex and in Triton X-100-solubilized membranes. In whole membranes cytochromes b, c, and a were reduced by succinate. In membranes from a mutant containing normal cytochromes but lacking succinate dehydrogenase no reduction of cytochrome was seen with succinate. It was concluded that the isolated succinate dehydrogenase-cytochrome b complex is a functional unit in the intact B. subtilis membrane. An accompanying paper describes cytochrome b as a structural unit involved in the membrane binding of succinate dehydrogenase.